Perfil do agricultor familiar cearense e a evolução da sua renda: uma análise do período de 2008 a 2011 - Medeiros, Maximiliano César Pedrosa Quintino de (2012)
The reduction of poverty, inequality in income distribution and, above all, the extinction of rural indigence are essential actions for a developing country, as these are very relevant factors and present among the great challenges in the process of promoting development in countries like Brazil, the Brazilian Northeast region, for example, has 27.55% of the country's population, but it has 56.34% of indigent individuals, while the State of Ceará has 4.4% of the Brazilian population, however, it comprises 9.23% of the indigent population and a large part of these people are in rural areas and survive from subsistence agriculture, so understanding and supporting Family Farmers is essential to bring about a radical change in this reality. Through the case study method, this work aims to analyze the profile of the Ceará family farmer and the evolution of income between the years 2008 to 2011. Initially, we will characterize the family farmer and verify some of the main public policies that are important for the development of Family Farming in Ceará and substantially relevant for the formation of family farmer's income. Then, qualitative analysis of the issues discussed is presented, through the verification of the database provided by the Technical Assistance and Rural Extension Company of Ceará (EMATERCE). Data analysis was performed through visual inspection of data on time series about the income variable, which allows verifying the evolution of income of the Ceará family farmer between the years 2008 to 2011. The conclusions evidenced a significant evolution in the income of the family farmer from Ceará, but the abyss of social inequality and the soreness of indigence still persisting in the reality of family farmer from Ceará.